"Papagaio véio não aprende a falá!?": um ensaio polifônico sobre os significados das vivências musicais em grupo de idosos portadores de doença de Parkinson - Coronago, Virginia Maria Mendes Oliveira (2009)
This study aimed to understand the meanings of the experience of Musical Experiences in a group of elderly patients of Parkinson's disease (PD), and integrate them into socially constructed meanings, through the ethnographic analysis interpretative. For this, as I support the theoretical framework of interpretative anthropology of Clifford Geertz. It is a methodological approach with qualitative research, conducted from the Project TAIP - Assistive Technology for Autonomy and Social Inclusion of elderly people with PD - developed at the Federal University of Santa Cantarina - UFSC (Florianópolis, SC) and the State University of Southwest Bahia, UESB (Campus Jequié - Bahia), locus of the research reported here. Four informants participated in the study, seniors who attended the group to experience music in different periods of two semesters during the year 2007. For the collection of information were conducted participant observations, semi-structured interviews in the homes of informants during the activity and after it ends. We identified the codes that indicate the meaning of the experience that , subsequently, served as a guide to the units of meaning and the construction of clusters of meanings: "The polyphony of meanings: the ill by DP to musical experiences - a career built"; Musical experience: the place of music in the context of the entire elderly person carrying the DP." Based on the results reflect a development based on the principles of the musician and neurologist Oliver Sacks in order to understand what is experienced with listening and make music. Completed with the consideration of the webs woven between the past and present expectations of future for this group of informants is a setup in search of better living through participation in activities that promote the welfare and social reintegration. All this confirms for the understanding of that music is an alternative, which allows to minimize the impacts caused by the DP, and its power and its relational space are important allies in the development of integrated health and welfare of human beings living / ages.